Gabon : 2019 Article IV Consultation, Fourth and Fifth Reviews under the Extended Arrangement under the Extended Fund Facility, and Request for Waiver of Nonobservance of Performance Criteria, and Rephasing of the Remaining Purchases; Press Release; Staff Report; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2020)
Prudent macroeconomic policies, supported by the Extended Arrangement, have contributed to Gabon's economic recovery. Growth is picking up, the fiscal and external positions have improved, public debt has started to decline, and Gabon has contributed to the rebuilding of regional international reserves. Challenges remain, though, as buffers are still insufficient and deep-rooted institutional and structural weaknesses continue to constraint growth and poverty reduction. Almost one-third of the population still lives below the poverty line.